2010
DOI: 10.1007/s12010-009-8779-5
|View full text |Cite
|
Sign up to set email alerts
|

Production and Stability of Protease from Candida buinensis

Abstract: Cow raw milk from dairy cooperatives was examined for its microbial composition. Among the isolates identified, 17.6% were yeasts. The most frequent genus was Candida, although members belonging to the genera Brettanomyces, Dekkera, and Geotricum were also identified. Although qualitative and quantitative tests for extracellular proteolytic activity were positive for all the species isolated, Candida buinensis showed the highest response (23.5 U/mg); therefore, it was selected for subsequent investigation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 38 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…The extracellular enzyme activities of yeast species can show variations between the strains of the same species. For example, the production of proteases is affected by growth conditions (such as components of medium, inoculum size and dissolved oxygen) and environmental factors (such as pH, temperature and incubation time) (de Araújo et al 2010;Molnárová et al 2014). In this study, it was observed that the proteolytic and lipolytic activities were strain-specific as previously stated.…”
Section: Screening Of Protease and Lipase Activitiessupporting
confidence: 71%
See 1 more Smart Citation
“…The extracellular enzyme activities of yeast species can show variations between the strains of the same species. For example, the production of proteases is affected by growth conditions (such as components of medium, inoculum size and dissolved oxygen) and environmental factors (such as pH, temperature and incubation time) (de Araújo et al 2010;Molnárová et al 2014). In this study, it was observed that the proteolytic and lipolytic activities were strain-specific as previously stated.…”
Section: Screening Of Protease and Lipase Activitiessupporting
confidence: 71%
“…The extracellular enzyme properties of yeast species may differ between strains of the same species. They can also be different depending on growth conditions and environmental factors (de Araújo et al 2010;Molnárová et al 2014;Delgado-Ospina et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in activation enthalpy (∆H), activation entropy (∆S), and Gibbs free energy (∆G) were calculated for the different temperatures as listed in Table 7. Positive ΔH values indicate that enzyme inactivation is an endothermic process [ 70 ]. The high values of ∆H° resulted from the thermal inactivation of β-galactosidase which indicates that the enzymatic activity undergoes a considerable change in conformation during denaturation [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several yeast strains belonging to the species A. pullulans , Y. lipolytica , and the genera Candida and Kluyveromyces have been described as protease producers. The production of proteases is strain specific and influenced by media components, physical factors such as pH and temperature, inoculum size, dissolved oxygen, and incubation time .…”
Section: Discussionmentioning
confidence: 99%